2020
DOI: 10.1186/s13018-020-02026-5
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics reveals the effect of lovastatin on steroid-induced necrosis of the femoral head in rabbits

Abstract: Purpose Lovastatin is an important medicine and it shows a significant effect against glucocorticoid-induced necrosis of the femoral head. This study aimed to investigate the effect of lovastatin on preventing necrosis of the femoral head of by serum metabolomics strategy. Methods Adult healthy adult Japanese white rabbits were divided into three groups: control group, model group, and drug group. The pathologic changes of femoral head were assessed with magnetic resonance imaging and microscope. Metabolomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…It was confirmed in previous studies that steroid use may result in changes in the lipid metabolism, which increase the risk of fat embolism[ 18 , 19 ]. Our team's studies also confirmed that GIONFH is closely related to the pathogenesis of lipid metabolism disorder induced by high-dose hormone in vivo[ 20 22 ]. Therefore, in order to further confirm the association between the onset of GIONFH and lipid metabolism disorder, a hypolipidemic drug group was added as comparative research to the Glucocorticoid-induced femoral head necrosis model rabbits in the animal experiment of this study.…”
Section: Introductionsupporting
confidence: 58%
“…It was confirmed in previous studies that steroid use may result in changes in the lipid metabolism, which increase the risk of fat embolism[ 18 , 19 ]. Our team's studies also confirmed that GIONFH is closely related to the pathogenesis of lipid metabolism disorder induced by high-dose hormone in vivo[ 20 22 ]. Therefore, in order to further confirm the association between the onset of GIONFH and lipid metabolism disorder, a hypolipidemic drug group was added as comparative research to the Glucocorticoid-induced femoral head necrosis model rabbits in the animal experiment of this study.…”
Section: Introductionsupporting
confidence: 58%
“…Lv et al (2022) found that the complex of Ganoderma lucidum polysaccharides and chromium had a significant impact on the regulation of glucose and lipid metabolism in high-fat and high-sugar diet rats, which was significantly influenced by the alpha linolenic acid metabolism pathway [69] . Besides, it was found that there existed a close correlation between alpha linolenic acid metabolism disorder and hyperuricemia and bone necrosis [70] , [71] . Pantothenate and CoA biosynthesis metabolic pathways were found that it had a close relationship with diabetes, nephropathy and iron deficiency anemia [72] , [73] , [74] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the crucial role glycerophospholipid metabolism plays in preserving skeletal integrity 45 . In the context of femoral head osteonecrosis, metabolomic investigations have pinpointed glycerophospholipid metabolism as a significant pathway implicated in the disease process 46 . Statin medications have shown efficacy in treating steroid-induced ischemic necrosis of the femoral head, potentially by ameliorating dysregulated glycerophospholipid metabolism 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%